Cost-Effectiveness of Clinical Decision Support to Improve CKD Outcomes Among First Nations Australians - Winnie Chen; Kirsten Howard; Gillian Gorham; Asanga Abeyaratne; Yuejen Zhao; Oyelola Adegboye; Nadarajah Kangaharan; Sean Taylor; Louise J. Maple-Brown; Samuel Heard; Mohammad Radwanur Talukder; Abdolvahab Baghbanian; et al. (Kidney International Reports)
Introduction: The Northern Territory (NT) is a hotspot for chronic kidney disease (CKD) and has a high incidence of kidney replacement therapy (KRT). The Territory Kidney Care clinical decision support (CDS) tool aims to improve diagnosis and management of CKD in remote NT, particularly among First Nations Australians. We model the cost-effectiveness of the CDS versus usual care. Methods: Taking a health care funder perspective, we modeled a cohort of people from remote NT at risk of or with CKD, as of January 1, 2017. A Markov cohort model was developed using 6 years of observed patient-level data (2017–2023), extrapolated to a 15-year time horizon. The CDS tool was modeled to improve CKD diagnosis (scenario 1), improve management (scenario 2), or improve both diagnosis and management (scenario 3). Results: The remote NT cohort consisted of 23,195 people, predominantly (89%) First Nations, with a mean age of 42 years. Scenario 3 (improved diagnosis and management) was most cost-effective at an incremental cost-effectiveness ratio (ICER) of $96,684 per patient avoiding KRT, $30,086 per patient avoiding death. Scenario 1 (improved diagnosis) was less cost-effective, and scenario 2 (improved management) was the least cost-effective. The ICER per quality-adjusted life years (QALYs) gained ranged from $3427 (scenario 3) to $63,486 (scenario 2). Conclusion: Territory Kidney Care is highly cost-effective when it supports early diagnosis of CKD and increases optimal management in diagnosed patients. These results support investing in CDS tools, implemented in strong partnerships, to improve outcomes in settings with a high burden of CKD.